After seventy-seven years Ptiloneuropsis Roesler (Psocodea: Psocomorpha: Ptiloneuridae) ceases to be a monotypic genus: a new species from Bahia, Brazil - Da Silva Neto, Alberto Moreira; Aldrete, Alfonso N. García; Rafael, José Albertino (Zootaxa, 2018)
A new species of Ptiloneuropsis from the Brazilian state of Bahia is here described and illustrated, it is based on male and female specimens; it differs from P. immaculata Roesler in details of the hypandrium and phallosome; the female is the first known in the genus.